An Improved C2oDE based on Stochastic Ranking - Si, Chengyong; Shen, Jianqiang; Wang, Chaofeng; Wang, Lei (Chinese Control Conference, 2021)
How to balance diversity and convergence as well as constraint violation and objective function in Constrained Optimization Problems (COPs) is an important and key issue when designing a new Constrained Optimization Evolutionary Algorithms (COEAs). C 2 oDE set a good example on this point, and obtains promising results. In C 2 oDE, the two Constraint Handling Techniques (CHTs) are adopted fixed in two phases. To verify whether there are some other more efficient combinations, Stochastic Ranking (SR) is adopted to balance the combination. Experimental results show a good performance, which also give some inspiration for other research.